Serum and urinary neutrophil gelatinase-associated lipocalin as a predictor of rat kidney histopathology in an early ischemia-reperfusion model (Medical Journal of Indonesia, 2012)
Background: The severity of ischemia-reperfusion (I/R) kidney injury is highly correlated with mortality and morbidity rate. Research on human and animal prove that NGAL predicts kidney injury at early phase. The objective of this study is to prove that the increase in serum and urinary NGAL are correlated with kidney tubular epithelial damage, and this increase has occurred in initiation phase, indicated by rat kidney histopathology in an early I/R model. Methods: Twenty eight male Sprague-Dawley rats were divided into 4 groups: 4 hour sham (Sham 4), 8 hour sham (Sham 8), 10 minute ischemia 4 hour reperfusion (I/R 4) and 10 minute ischemia 8 hour reperfusion (I/R 8). Blood, urine and kidney samples were collected. Serum creatinine level was analyzed with Jaffe method, while serum and urinary NGAL level were analyzed with direct sandwich ELISA method. Evaluation of kidney damage were measured semi quantitatively in tissue stained with HE. Further evaluation to confirm cellular changes on kidney was performed by electron microscope and immunohistochemistry. Results: Serum NGAL was found significantly correlated with degree of kidney tissue damage (ρSpearman NGAL serum = 0.701, p < 0.001), also urinary NGAL (ρSpearman = 0.689, p < 0.001). NGAL expression differs significantly between I/R group and sham (t-test, t = -26635.056, p < 0.001), also kidney damage (t-test, t = -5.028, p < 0.001), and serum and urinary NGAL levels (Mann-Whitney, U = 0, p < 0.001). With cutoff points of 136.95 ng/mL and 58.69 ng/mL subsequently for serum and urinary NGAL , it is found that sensitivity = 1, specificity = 1. Conclusion: Elevation of serum and urinary NGAL are significantly correlated with epithelial tubular kidney damage on rat undergoing early ischaemia reperfusion. (Med J Indones. 2012;21:208-13)